2020
DOI: 10.1002/chem.202002966
|View full text |Cite
|
Sign up to set email alerts
|

Amine Catalysis with Substrates Bearing N‐Heterocyclic Moieties Enabled by Control over the Enamine Pyramidalization Direction

Abstract: Stereoselective organocatalytic C−C bond formations that tolerate N‐heterocycles are valuable since these moieties are common motifs in numerous chiral bioactive compounds. Such transformations are, however, challenging since N‐heterocyclic moieties can interfere with the catalytic reaction. Here, we present a peptide that catalyzes conjugate addition reactions between aldehydes and nitroolefins bearing a broad range of different N‐heterocyclic moieties with basic and/or H‐bonding sites in excellent yields and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…27 Mechanistic studies, including back‐reaction monitoring of quasi‐enantiomers by mass spectrometry, [15] revealed that the intermediate enamine is involved in the rate‐ and enantioselectivity determining step [14–17,28] . Further studies showed how the reactivity and stereoselectivity of peptide catalysts can be improved by (a) tuning the trans : cis ratio of the tertiary d Pro‐Pro bond (Scheme 2a) [29] and (b) endowing the enamine with an endo ‐pyramidalized enamine‐N (Scheme 2b) [18,30] . These insights allowed us to establish catalyst H−Oic‐ d Pip‐ d Glu−NH 2 ( B , H−Oic−OH: (2 S ,3a S ,7a S )‐octahydro‐1 H ‐indole‐2‐carboxylic acid; H−Pip−OH: ( R )‐piperidine‐2‐carboxylic acid) for conjugate addition reactions with nitroolefins bearing N‐heterocycles [18] .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…27 Mechanistic studies, including back‐reaction monitoring of quasi‐enantiomers by mass spectrometry, [15] revealed that the intermediate enamine is involved in the rate‐ and enantioselectivity determining step [14–17,28] . Further studies showed how the reactivity and stereoselectivity of peptide catalysts can be improved by (a) tuning the trans : cis ratio of the tertiary d Pro‐Pro bond (Scheme 2a) [29] and (b) endowing the enamine with an endo ‐pyramidalized enamine‐N (Scheme 2b) [18,30] . These insights allowed us to establish catalyst H−Oic‐ d Pip‐ d Glu−NH 2 ( B , H−Oic−OH: (2 S ,3a S ,7a S )‐octahydro‐1 H ‐indole‐2‐carboxylic acid; H−Pip−OH: ( R )‐piperidine‐2‐carboxylic acid) for conjugate addition reactions with nitroolefins bearing N‐heterocycles [18] .…”
Section: Methodsmentioning
confidence: 99%
“…Secondary amines catalyze this reaction by the formation of an enamine with the aldehyde followed by reaction with the nitroolefin [12–17] . Despite more than 500 reports, only a few examples with nitroolefins bearing N‐heterocyclic substituents have been reported [18–20] . Only a single study used, in a cascade reaction, an aldehyde with an N‐heterocyclic moiety (Scheme 1b) [21] …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, systematic investigations using heterocyclic nitroalkenes are very rare. Only very recently, Wennemers described peptide catalyzed Michael reactions of nitroalkenes bearing N-heterocycles …”
Section: Introductionmentioning
confidence: 99%